Tea plantations and their importance as host plants and hot spots for epiphytic cryptogams - Grzegorz J. Wolski (Nature Portfolio, 2021)
Abstract Bryophytes and lichens are outstanding bioindicators, not only of the plant community in which they develop, but also the substrates on which they grow. Some epiphytic cryptogams, particularly the rare ones, are stenotopic and require a long habitat continuity, for example substrates such as old trees. It could also be a tea plantation, this is because the shrubs are not felled, and most of them may have several dozen years. In addition, the shrubs are not subject to sudden changes in microclimatic conditions as only the young leaves are harvested. As the importance of tea plantations as host plants for mosses and lichens has not yet been studied, the present study examines the species diversity of cryptogams of two tea plantations in Georgia (Caucasus). The study also examines the phytogeography, spatial pattern, environmental conditions and ecological indicators of the cryptogams. Thirty-nine cryptogam taxa were identified; typical forest taxa dominated, even in the absence of typical forest communities. Some of these species are obligatory epiphytes, rare or even critically endangered in most European countries (e.g., Orthotrichum stellatum, O. stramineum, Lewinskya striata). The fairly abundant record of such species on tea plantations indicates the importance of these phytocoenoses for the preservation of rare species, and indicates that these habitats are hot spots for these cryptogams in otherwise changed envirnonment. Additionally, as indicated the analysis of the species composition of individual plantations and the mathematical analysis made on this basis, plantations differ from each other. Another interesting result is also the spatial distributions of cryptogams on tea bushes resemble those of forest communities and lichens seems to be more sensitive than bryophytes to antropogenic changes of environment.